2005
DOI: 10.1016/j.cmet.2005.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Tmem27: A cleaved and shed plasma membrane protein that stimulates pancreatic β cell proliferation

Abstract: The signals and molecular mechanisms that regulate the replication of terminally differentiated beta cells are unknown. Here, we report the identification and characterization of transmembrane protein 27 (Tmem27, collectrin) in pancreatic beta cells. Expression of Tmem27 is reduced in Tcf1(-/-) mice and is increased in islets of mouse models with hypertrophy of the endocrine pancreas. Tmem27 forms dimers and its extracellular domain is glycosylated, cleaved and shed from the plasma membrane of beta cells. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
142
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 53 publications
7
142
1
Order By: Relevance
“…This is consistent with the observed role of glutamine in the release of insulin from pancreatic ␤-cells (38). We could detect B 0 AT1 mRNA in pancreas but do not know whether it is expressed in ␤-cells, where the B 0 AT1 trafficking subunit collectrin has been found (39,40). It has been reported that some strains of C57Bl/6J mice have deletions in the nicotinamide nucleotide transhydrogenase (Nnt), resulting in a reduced insulin response (17).…”
Section: Discussionsupporting
confidence: 74%
“…This is consistent with the observed role of glutamine in the release of insulin from pancreatic ␤-cells (38). We could detect B 0 AT1 mRNA in pancreas but do not know whether it is expressed in ␤-cells, where the B 0 AT1 trafficking subunit collectrin has been found (39,40). It has been reported that some strains of C57Bl/6J mice have deletions in the nicotinamide nucleotide transhydrogenase (Nnt), resulting in a reduced insulin response (17).…”
Section: Discussionsupporting
confidence: 74%
“…Additionally, down-regulation of Gch1 is associated with hyperglycemia secondary to progressive ␤-cell dysfunction (impaired glucose-stimulated insulin secretion) and ␤-cell loss (reduced number and proliferation) in Tcf1 (hepatocyte nuclear factor 1-␣) knock-out mice (data from Ref. 29 and associated Gene Expression Omnibus (GEO) dataset GSE3544). Gch1 is a crucial (rate-limiting) component of the tetrahydrobiopterin synthetic pathway and has been directly implicated in diabetes-associated endothelial dysfunction through its critical role in nitric oxide (NO) synthesis (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal domain of Tmem27 appears to be involved implication in glucose-stimulated insulin exocytosis and and/or ß-cell mass in pancreas, 67,68 as well as renal collecting duct primary cilium formation and polycystic kidney disease. 70 As described more in detail in later paragraphs, Tmem27 has also been shown to be critical for the correct expression of amino acid transporters in kidney.…”
Section: 11mentioning
confidence: 99%
“…65 Tmem27 has been shown to be expressed in liver, lung, endocrine pancreas and kidney proximal tubule brush border membrane and collecting duct, hence the misleading name Collectrin. 12,13,67,68 Given the lack of Tmem27 catalytic activity, it does not seem to play a role in the classical RAS although an implication in the development of salt sensitive hypertension has been suggested. 69 Tmem27 has been shown to bind proteins involved in intracellular and membrane protein trafficking and ciliary movement such as γ-actin-myosin II-A, snapin, SNAP-25 and polycystin-2-polaris complexes.…”
mentioning
confidence: 99%